The Influence of Self-Potential and School Environment on Students' Career Development through the Double Track Program - Risma Nur Azizah; Wilis Werdiningsih (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This study focuses on the career development of students at the senior secondary education level. The purpose of this research is to analyze the influence of self-potential and the school environment on students’ career development through the mediating role of the Double Track Program at SMAN Pilangkenceng. This study employs a quantitative approach using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Data were collected through questionnaires from 92 students participating in the Double Track Program. The study hypothesizes that self-potential and the school environment have a significant influence on career development, both directly and through the mediating program. The findings indicate that the school environment has a positive and significant effect on students’ career development, both directly and through the Double Track Program, while self-potential shows no significant effect. This research contributes to the field of educational management by highlighting the effectiveness of the Double Track Program as a vocational innovation linking the educational environment with career readiness. The results emphasize the importance of strengthening school support and optimizing program implementation to enhance students’ employability and future career success.